2017
DOI: 10.1098/rsfs.2016.0088
|View full text |Cite
|
Sign up to set email alerts
|

Energetics in robotic flight at small scales

Abstract: Recent advances in design, sensing and control have led to aerial robots that offer great promise in a range of real-world applications. However, one critical open question centres on how to improve the energetic efficiency of aerial robots so that they can be useful in practical situations. This review paper provides a survey on small-scale aerial robots (i.e. less than 1 m 2 area foot print, and less than 3 kg weight) from the point of view of energetics. The paper discusses methods to improve the efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 86 publications
(172 reference statements)
1
50
0
Order By: Relevance
“…In recent times, there has been an explosion of research on microaerial vehicles (MAVs), ranging from low‐level control (Lee, Leok, & McClamroch, ) to high‐level, specification‐based planning (Wolff, Topcu, & Murray, ). One class of MAVs, the quadrotor, has become popular in academia and industry alike due to its mechanical and control simplicity, high maneuverability, and low cost of entry point compared to other aerial robots (Karydis & Kumar, ). Indeed, there have been numerous applications of quadrotors to fields such as intelligence, surveillance and reconnaissance, aerial photography, structural inspection (Özaslan et al., ), robotic first responders (Mohta et al., ), and cooperative construction (Augugliaro et al., ) and aerial manipulation (Thomas, Loianno, Polin, Sreenath, & Kumar, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there has been an explosion of research on microaerial vehicles (MAVs), ranging from low‐level control (Lee, Leok, & McClamroch, ) to high‐level, specification‐based planning (Wolff, Topcu, & Murray, ). One class of MAVs, the quadrotor, has become popular in academia and industry alike due to its mechanical and control simplicity, high maneuverability, and low cost of entry point compared to other aerial robots (Karydis & Kumar, ). Indeed, there have been numerous applications of quadrotors to fields such as intelligence, surveillance and reconnaissance, aerial photography, structural inspection (Özaslan et al., ), robotic first responders (Mohta et al., ), and cooperative construction (Augugliaro et al., ) and aerial manipulation (Thomas, Loianno, Polin, Sreenath, & Kumar, ).…”
Section: Introductionmentioning
confidence: 99%
“…A paper by [15] showed that energy consumption increases with forward velocity after a first decrease, when compared to the energy consumption in a hover condition. Another study by [16] evaluated the direct relation between energy efficiency and the speed of a multi-rotor system.…”
Section: Relevant Workmentioning
confidence: 99%
“…The total thrust required to stay airborne would be T = mg (cos θ cos φ) . If the yaw angle is fixed to zero and T from the above equation is substituted in equations of motion, the multi-rotor equations of motion can be reduced to Equations (14) and (15).…”
Section: Model Of the Evaluated Systemmentioning
confidence: 99%
“…Recent advances in the field of aerial robotics and sensor technologies have greatly enhanced the capabilities of unmanned aerial vehicles (UAVs). One consequence of this outcome has been the growing interest in multi-aerial vehicle applications [1], [2], [3]. Clear benefits of multi-drone systems are envisioned for a wide range of missions including search and rescue [4], long-term monitoring [5], sensor data collection [6], indoor navigation [7], environment exploration [8] and cooperative grasping and transportation [9].…”
Section: Introductionmentioning
confidence: 99%